8-Hydroxyquinolin-N-oxide-Promoted Copper-Catalyzed C–S Cross-Coupling of Thiols with Aryl Iodides - Su, Kun; Qiu, Yatao; Yao, Yiwu; Zhang, Dayong; Jiang, Sheng (Synlett, 2012)
8-Hydroxyquinolin-N-oxide was identified as a superior ligand for CuI-catalyzed C–S coupling reactions of aryl iodides with thiols to afford the corresponding thioethers in excellent yield. The method shows excellent chemoselectivity and high functional-group tolerance in both coupling partners.
Keywords: C–S coupling reactions; copper; cross-coupling; 8-hydroxyquinolin-N-oxide; Ullmann reaction